2016
DOI: 10.1038/srep34369
|View full text |Cite
|
Sign up to set email alerts
|

Animal choruses emerge from receiver psychology

Abstract: Synchrony and alternation in large animal choruses are often viewed as adaptations by which cooperating males increase their attractiveness to females or evade predators. Alternatively, these seemingly composed productions may simply emerge by default from the receiver psychology of mate choice. This second, emergent property hypothesis has been inferred from findings that females in various acoustic species ignore male calls that follow a neighbor’s by a brief interval, that males often adjust the timing of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Common foci are the relationship between synchronization and prosociality (Gebauer et al, 2016; Reddish et al, 2016; Rennung and Göritz, 2016; Tunçgenç and Cohen, 2016; Cirelli et al, 2017), and different forms of rhythmic behaviors in interaction (Large and Gray, 2015; Ravignani, 2015; Yu and Tomonaga, 2015; Ellamil et al, 2016; Gebauer et al, 2016; Greenfield et al, 2016; Moore et al, 2016; Schirmer et al, 2016; Wallot et al, 2016; Murphy and Schul, 2017). …”
Section: Rhythm In Other Journals Since Late 2015mentioning
confidence: 99%
“…Common foci are the relationship between synchronization and prosociality (Gebauer et al, 2016; Reddish et al, 2016; Rennung and Göritz, 2016; Tunçgenç and Cohen, 2016; Cirelli et al, 2017), and different forms of rhythmic behaviors in interaction (Large and Gray, 2015; Ravignani, 2015; Yu and Tomonaga, 2015; Ellamil et al, 2016; Gebauer et al, 2016; Greenfield et al, 2016; Moore et al, 2016; Schirmer et al, 2016; Wallot et al, 2016; Murphy and Schul, 2017). …”
Section: Rhythm In Other Journals Since Late 2015mentioning
confidence: 99%
“…Studies have shown that synchronized calling can increase success of reproduction, attract females, and mislead predators (Vasconcelos et al 2012, Greenfield et al 2016). In our study, calling was more synchronized in time for stations that were closer to -19, 2017 each other than for stations that were further apart.…”
Section: Synchronized Calling May Facilitate Reproductive Successmentioning
confidence: 99%
“…Some of the best‐studied examples of chorusing in animals involve males vocalizing together during courtship displays . These studies suggest that animal chorusing evolved in part to increase callers’ attractiveness to females or to deter predators . For instance, in a study of Túngara frogs ( Physalaemus pustulosus ), Ryan and colleagues showed that males call in chorus function to maximize overall sound intensity, hence attracting females from further distances, or to obscure an individual's precise location, mitigating predation risk.…”
Section: Temporal Patterning In Animal Vocalizationmentioning
confidence: 99%